PENGARUH ENTREPRENEURIAL SELF-EFFICACY TERHADAP GREEN ENTREPRENEURIAL INTENTION YANG DIMEDIASI OLEH PENDIDIKAN KEWIRAUSAHAAN : Survei Pada Mahasiswa Start-Up Fakultas Pendidikan Ekonomi Dan Bisnis Universitas Pendidikan Indonesia - Linda Maryani, - (2023)
ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh Entrepreneurial Self-Efficacy terhadap Green Entrepreneurial Intention dan Pendidikan Kewirausahaan pada Mahasiswa Startup Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia serta mengetahui Pendidikan Kewirausahaan memediasi pengaruh Entrepreneurial Self-Efficacy terhadap Green Entrepreneurial Intention pada Mahasiswa Startup Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia. Metode yang digunakan dalam penelitian ini adalah metode survey dan instrument yang digunakan berupa angket sebagai alat pengumpul data yang disebarkan kepada Mahasiswa Star-Up Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia dengan Teknik Purposive Sampling dan jumlah sampel sebanyak 207 responden. Subjek penelitian ini adalah Mahasiswa Startup Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia. Temuan dalam penelitian ini terdapat pengaruh positif variabel Entrepreneurial Self-Efficacy terhadap Green Entrepreneurial Intention serta Pendidikan Kewirausahaan mampu memediasi Entrepreneurial Self-Efficacy terhadap Green Entrepreneurial Intention. Adapun saran dari penelitian ini dalam Variabel Green Entrepreneurial Intention terdapat indikator desire yakni mahasiswa harus meningkatkan keyakinan terhadap kemampuan diri, pengendalian diri dalam membangun usaha yang mengutamakan kelestarian lingkungan, sementara pada variabel Entrepreneurial Self-Efficacy terdapat indikator planning dan marshaling bahwa mahasiswa memerlukan kemampuan yang komunkatif dalam menjalin hubungan dengan lingkungan sosial di masyarakat. Kata Kunci: Entrepreneurial Self-Efficacy, Green Entrepreneurial Intention, Pendidikan Kewirausahaan ABSTRACT The purpose of this study was to obtain information about the effect of Entrepreneurial Self-Efficacy on Green Entrepreneurial Intention and Entrepreneurial Education in Startup Students at the Faculty of Economics and Business Education, Indonesian University of Education and to find out that Entrepreneurship Education mediates the effect of Entrepreneurial Self-Efficacy on Green Entrepreneurial Intention in Startup Students at the Faculty of Economics and Business Education Indonesian education university. The method used in this study was a survey method and the instrument used was a questionnaire as a data collection tool which was distributed to the Start-Up Students of the Faculty of Economics and Business Education, Indonesian University of Education with the Purposive Sampling Technique and a total sample of 207 respondents. The subjects of this research were Startup Students of the Faculty of Economics and Business Education, Indonesian University of Education. The findings in this study are the influence of Entrepreneurial Self-Efficacy variables on Green Entrepreneurial Intention and Entrepreneurial Education being able to mediate Entrepreneurial Self-Efficacy on Green Entrepreneurial Intention. The suggestion from this study is that in the Green Entrepreneurial Intention Variable there is an indicator of desire, namely students must increase confidence in their own abilities, self-control in building a business that prioritizes environmental sustainability, while in the Entrepreneurial Self-Efficacy variable there are indicators of planning and marshaling that students need communicative abilities. in establishing relationships with the social environment in society. Keywords: Entrepreneurial Self-Efficacy, Green Entrepreneurial Intention, Entrepreneurship Education